For your first question, they've already given you the value of f(x) and g(x) so all you want to do is plug it into the equation. :) \[f(x) = 9x + 4 \] \[ g(x) = -5x + 1\] Therefore g(x) - f(x) would equal: \[-5x + 1 - ( 9x + 4) = ? \]
For the next question: f (x) = 9x - 5 f (2) = 9(2) - 5 = ? Then after you find out what f(2) equals to, we want to find what g(4) equals to. So, g (x) = 6x g (4) = 6(4) = ? Then f(2) - g(4) = ?
they are easy just try to simply solve it
not quiteeee. So what did you get for f(2) = ?
Note: f(2) = 9(2) - 5 = 18 - 5 = 13 g(4) = 6(4) = 24 f(2) - g(4) = 13 - 24 = ?
oh ok so it would be -11
For question 3. You need to multiply both f(x) and g(x) together. Since \[f(x) = x^2 + 6x\] and \[g(x) = 2x^3\] Multiply both together and we get: \[f(x) \times g(x) = 2x^3 (x^2 + 6x) = ?\]
multiply the numbers and the powers will add
would is be D?
now for the final one. Just multiply both and see which one is correct. So what do you get when you multiply f(x) and g(x) together? \[f(x) \times g(x) = 5x ( 3x - 2) = ?\]
would the answer be A?
yes A is correct but have you checked option C or D? Remember that the question says "check all correct answer(s)" :)
so A, C and D are the correct answers
A is correct. C is correct. But what about D?? Note: when you multiply anything by 0, the answer will be 0
so D is incorrect